Managing the foreign investment portfolio: How industry and governance diversity influence firm performance. Issue 6 (December 2016) - Chen, Chung-Jen; Lin, Ya-Hui
Highlights: Governance diversity has an inverse U-shaped relationship to firm performance, whereas industry diversity does not. R&D capability positively moderates the relationship between industry diversity and firm performance. Industry profitability negatively moderates the relationship between industry diversity and firm performance. Industry profitability negatively moderates the relationship between governance diversity and firm performance. The empirical findings of our study are useful for firms that invest in emerging economies. Abstract: Foreign investment has been seen as an important strategy for learning about new technologies and markets. However, the link between the characteristic of a foreign investment portfolio and firm performance has not been examined in detail. Using panel data from 199 Taiwanese firms, this study examines how the foreign investment portfolio in terms of industry and governance diversity influences firm performance. This study finds that governance diversity has an inverse U-shaped relationship to firm performance, whereas industry diversity does not. In addition, this study also finds that their relationships are affected by R&D capability and industry profitability. The empirical findings of our study are useful for firms that invest in emerging economies.